2004
DOI: 10.1002/ajh.20012
|View full text |Cite
|
Sign up to set email alerts
|

Second malignant neoplasms in childhood acute lymphoblastic leukemia: Primitive neuroectodermal tumor of the chest wall with germline p53 mutation as a second malignant neoplasm

Abstract: About 80% of children treated for acute lymphoblastic leukemia (ALL) will be long-term survivors. Second malignant neoplasm (SMNs) are a devastating sequelae observed on these children, with an estimated cumulative risk of 2-3.3% fifteen years after diagnosis. Primitive neuroectodermal tumor of bone (PNET) is rarely observed as a SMN following treatment of childhood ALL. The authors described the occurrence of a chest wall PNET of the bone at the site of a central line placement associated with both germ-line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…Acute lymphoid leukemia (ALL) is the main kind of leukemia that occurs in children. Although about 80% of children diagnosed with ALL can attain complete remission and be long-term survivors with current treatment protocols [12], the prognosis of many individuals, such as those with Philadelphia chromosome positive (Ph + ) ALL and HTLV-I-associated adult T-cell leukemia, is still very poor [13,14]. There-fore, finding new antileukemia drugs and effective therapies for the clinical treatment of myeloid leukemia will remain an important area of research.…”
Section: Discussionmentioning
confidence: 99%
“…Acute lymphoid leukemia (ALL) is the main kind of leukemia that occurs in children. Although about 80% of children diagnosed with ALL can attain complete remission and be long-term survivors with current treatment protocols [12], the prognosis of many individuals, such as those with Philadelphia chromosome positive (Ph + ) ALL and HTLV-I-associated adult T-cell leukemia, is still very poor [13,14]. There-fore, finding new antileukemia drugs and effective therapies for the clinical treatment of myeloid leukemia will remain an important area of research.…”
Section: Discussionmentioning
confidence: 99%
“…PNETs are rarely observed as SMNs [12,40,41]. To our knowledge, this is the first report of a PNET that developed in pediatric patients treated for hepatoblastoma.…”
Section: Discussionmentioning
confidence: 85%
“…Although a recent study evaluating the prevalence of germline mutations in children with cancer identified TP53 mutations in 4 of 46 patients with Ewing sarcoma, 26 there traditionally has been consensus that these mutations are not associated with Ewing sarcoma (F 1 sarcoma) susceptibility. 5 In our own review of the International Agency for Research on Cancer TP53 database R17 (released November 2013), an online resource providing information regarding the TP53 mutation characteristics and malignancies previously published in TP53 germline mutation carriers, we identified 177 osteosarcomas (approximately 7% of all cancers documented in the database) as opposed to 2 possible cases of Ewing sarcoma (<0.1% of registered cancers): 1 reported case of an Askin tumor with immunohistochemical findings consistent with Ewing sarcoma but no data regarding fusion status 27 and 1 case of Ewing sarcoma reported anamnestically in a family member of a TP53 mutation carrier. 28 Two additional cases of Ewing sarcoma included in the International Agency for Research on Cancer database could not be confirmed by review of the reference publication.…”
Section: Discussionmentioning
confidence: 99%